Understanding utterances : The need for pragmatic competence / Kamisah Ariffin - Ariffin, Kamisah (Universiti Teknologi MARA Cawangan Pahang, 2004)
The colossal time spent on learning grammatical rules of a language may still not make a learner proficient in that language. The sociolinguistics perspectives have moved to the notion that there is more to learning a language than learning about rules and grammar. Since the use of a language is seen as a social activity, the concept of 'communicative competence', that is, knowing what to say, to whom, and how to say it appropriately was seen as an important element of teaching a language (Hymes 1965; Saville-Troike 1985). However, this concept is enormously complex. Before a speaker should know what to say and to whom in an appropriate way, s/he needs another competence, i.e pragmatic competence, to understand the meaning of utterances in context. This is because the divergent of what is said and what is implied have made communication difficult with many opportunities for mistakes and understanding to occur. This paper addresses the need of pragmatic competence to be taught along the other language skills.